2014
DOI: 10.4236/jbnb.2014.53019
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Impregnation of Essential Bark Oil in Copolymers of L-Lactide with 7-Membered Cyclic Compounds

Abstract: In order to develop a novel controlled-release material, we previously attempted to impregnate poly(L-lactide) (poly(L-LA)), poly(L-LA-ran-CL) (CL: ε-caprolactone) or poly(L-LA-ran-TEMC) (TEMC: tetramethylene carbonate) with low boiling point, organic useful compounds using supercritical carbon dioxide (scCO2) as the solvent. In this work, the factors influencing impregnation of poly (L-LA) random copolymers with useful compounds were investigated under scCO2 using the copolymers previously used. The influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…The SSI was also reported for efficient loading of bark essential oil from Thujopsis dolabrata var. hondae and clove oil into poly(lactic acid) and polyethylene based films for food packaging, respectively [49,50].…”
mentioning
confidence: 99%
“…The SSI was also reported for efficient loading of bark essential oil from Thujopsis dolabrata var. hondae and clove oil into poly(lactic acid) and polyethylene based films for food packaging, respectively [49,50].…”
mentioning
confidence: 99%
“…The proportion of the copolymers obtained from the ACOP process was almost the same as that in the feed ratio similarly to conventional polymerization with monomer purification and gas replacement. In prior work, the T m and Δ H m values of copolymers of L‐LA with CL, TEMC and DXO were lowered remarkably as the L‐LA content was decreased, and the copolymers containing approximately 70% L‐LA had low degrees of crystallinity . A poly(L‐LA‐ ran ‐VL) specimen having an 85/15 composition had a T m of 153.2°C and a 28.9 J/g Δ H m value, while an 83/17 specimen synthesized by the ACOP method had values of 173.8°C and 35.4 J/g.…”
Section: Resultsmentioning
confidence: 95%
“…In prior work, essential bark oil has been incorporated into copolymers of L‐LA with CL, TEMC, or DXO at high concentrations using scCO 2 . During these trials, partial melting of the polymer surfaces was observed during processing with scCO 2 , even at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, scCO 2 can be used to combine these materials at low temperatures to produce composites based on the incorporation of oils in biodegradable polymers, with the aim of obtaining the spontaneous release of the oil vapors when required. To date, this technique has been applied to encapsulate oils in poly(L-lactide) [poly(L-LA)] or copolymers consisting of L-LA with other cyclic compounds 2427 . Such technology could result in minimal environmental impact as well as lower energy usage and a reduction in labor.…”
Section: Introductionmentioning
confidence: 99%